Highly stretchable and robust transparent conductive polymer composites for multifunctional healthcare monitoring - Anky Fitrian Wibowo; Joo Won Han; Jung Ha Kim; Ajeng Prameswati; Siti Aisyah Nurmaulia Entifar; Jihyun Park; Jonghee Lee; Soyeon Kim; Dong Chan Lim; Myoung-Woon Moon; Min-Seok Kim; Yong Hyun Kim (Science and Technology of Advanced Materials)
Soft, stretchable, conductive thin films have propelled to the forefront of applications in stretchable sensors for on-skin health monitoring. Stretchable conductive films require high conformability, stretchability, and mechanical/chemical stability when integrated into the skin. Here, we present a highly stretchable, conductive, and transparent natural rubber/silver nanowire (AgNW)/poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) composite film. Overcoating the PEDOT:PSS layer results in outstanding mechanical robustness and chemical stability by suppressing the mechanical and chemical degradation of the nanowire networks. Moreover, the introduction of the organic surface modifier enhances the bonding strength between the natural rubber substrate and AgNW at the interface. The highly conformable composite films are integrated into multifunctional on-skin sensors for monitoring various human motions and biological signals with low-power consumption. We believe that the highly stretchable, robust, and conformable natural rubber/AgNW/PEDOT:PSS composite film can offer new opportunities for next-generation wearable sensors for body motion and physiological monitoring.